2018
DOI: 10.20944/preprints201803.0138.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoluminescence Study of the Influence of Additive Ammonium Hydroxide in Hydrothermally Grown ZnO Nanowires

Abstract: We report the influence of ammonium hydroxide (NH4OH), as growth additive, on zinc oxide nanomaterial through the optical response obtained by photoluminescence (PL). A lowtemperature hydrothermal process is employed for the growth of ZnO nanowires (NWs) on seedless Au surface. A more than two order of magnitude change in ZnO NW density is demonstrated via careful addition of NH4OH in the growth solution. Further, we show by systematic experimental study and PL characterization data that the addition of NH4OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…On seedless Au substrate, Boubenia et al [36,47] controlled both ZnO NW density and their electrical properties via developed low-cost and scalable bottom-up hydrothermal growth process using NH 4 OH addition. They found that small increase in pH value leads to increase the NW densities, Figure 10.…”
Section: Growth Solution Ph Valuementioning
confidence: 99%
“…On seedless Au substrate, Boubenia et al [36,47] controlled both ZnO NW density and their electrical properties via developed low-cost and scalable bottom-up hydrothermal growth process using NH 4 OH addition. They found that small increase in pH value leads to increase the NW densities, Figure 10.…”
Section: Growth Solution Ph Valuementioning
confidence: 99%